Influenza A(H3N2) infection followed by separate COVID-19 infection - Tatiana Schäffer Gregianini; Richard Steiner Salvato; Ludmila Fiorenzano Baethgen; Cláudia Fasolo Piazza; Regina Bones Barcellos; Fernanda Marques Godinho; Ana Beatriz Gorini da Veiga (Pan American Health Organization, 2023)
This study describes the case of a health professional infected first by influenza virus A(H3N2) and then by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 11 days later. Respiratory samples and clinical data were collected from the patient and from close contacts. RNA was extracted from samples and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to investigate the viruses. The patient presented with two different illness events: the first was characterized by fever, chest and body pain, prostration and tiredness, which ceased on the ninth day; RT-qPCR was positive only for influenza virus A(H3N2). Eleven days after onset of the first symptoms, the patient presented with sore throat, nasal congestion, coryza, nasal itching, sneezing and coughing, and a second RT-qPCR test was positive only for SARS-CoV-2; in the second event, symptoms lasted for 11 days. SARS-CoV-2 sequencing identified the Omicron BA.1 lineage. Of the patient's contacts, one was coinfected with influenza A(H3N2) and SARS-CoV-2 lineage BA.1.15 and the other two were infected only with SARS-CoV-2, one also with Omicron BA.1.15 and the other with BA.1.1. Our findings reinforce the importance of testing for different viruses in cases of suspected respiratory viral infection during routine epidemiological surveillance because common clinical manifestations of COVID-19 mimic those of other viruses, such as influenza.